A mechanism of release of calreticulin from cells during apoptosis. - Tarr, J; Young, P; Morse, R; Shaw, D; Haigh, R; Petrov, P; Johnson, S; Winyard, P; Eggleton, P (2010)
Calreticulin (CRT) is an endoplasmic reticulum (ER) chaperone responsible for glycoprotein folding and Ca(2+) homeostasis. CRT also has extracellular functions, e.g. tumor and apoptotic cell recognition and wound healing, but the mechanism of CRT extracellular release is unknown. Cytosolic localization of CRT is determined by signal peptide and subsequent retrotranslocation of CRT into the cytoplasm. Here, we show that under apoptotic stress conditions, the cytosolic concentration of CRT increases and associates with phosphatidylserine (PS) in a Ca(2)(+)-dependent manner. PS distribution is regulated by aminophospholipid translocase (APLT), which maintains PS on the cytosolic side of the cell membrane. APLT is sensitive to redox modifications of its SH groups by reactive nitrogen species. During apoptosis, both CRT expression and the concentration of nitric oxide (NO) increase. By using S-nitroso-l-cysteine-ethyl-ester, an intracellular NO donor and inhibitor of APLT, we showed that PS and CRT externalization occurred together in an S-nitrosothiol-dependent and caspase-independent manner. Furthermore, the CRT and PS are relocated as punctate clusters on the cell surface. Thus, CRT induced nitrosylation and its externalization with PS could explain how CRT acts as a bridging molecule during apoptotic cell clearance.